Influence of Mobile Phase Additives on Ionization Efficiency of Androgenic Anabolic Steroids in LC-positive ESI/MS - Jeong, Tae Young; Kang, Minsik; Lee, Kang Mi; Oh, Han Bin; Lee, Jae Ick (AOMSC-KSMS 2023, 2023)
Androgenic anabolic steroids (AAS) are synthetic analogues of the male hormone testosterone and widely misused to enhance athletic performance in sports. Therefore, developing and updating analytical methods is important to prevent the illegal abuse of AAS. However, current analysis of AAS using LC-ESI/MS suffers from sensitivity problem resulting from the low/poor ionization efficiency of AAS in ESI. Therefore, this study aims to investigate the influence of mobile phase additives to improve the ionization efficiency of AAS in positive ESI, and evaluate the relationship between AAS structure, ionization efficiency and additives. The ionization efficiency of 68 AAS were evaluated under 31 mobile phase composition conditions with different additives (no additive, formic acid, acetic acid, ammonium formate, ammonium acetate and ammonium fluoride) and concentrations. As results, regarding to the C3 structure of AAS, the conjugated-keto, unconjugated-keto with oxygen and conjugated-hydroxyl structures showed better ionization efficiency than unconjugated-keto and unconjugated-hydroxyl structures in all the additive. Also, it was observed that ammonium formate and ammonium fluoride additives improved the ionization efficiency of AAS including conjugated-keto or unconjugated-keto with oxygen, compared to formic acid additive. In conclusion, this information should be valuable for development of high sensitive multi-residue analytical method of AAS.